Analysis of the Relationship between R&D and Company Performance - Weber, Nadine; Tyll, Ladislav; Balogh, Ivan; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2023)
Research and development (R&D) activities are crucial to remain competitive. Extant literature presents divergent views on R&D’s contribution to company performance, specifically profitability and hints at cultural differences in approaching R&D led to analyze such relationship within a regional comparison between Europe and Asia. Filling the research gap focusing on the Technology, Media and Telecommunication (TMT) sector, the study evaluated a sample of 132 Asian and European companies operating in the TMT sector for the 2018 – 2022 period. Using panel generalized method of moments (P-GMM), results showed R&D intensity had a positive but statistically insignificant impact on profitability, but a positive and significant effect on capital market performance. Notably, Asian firms' R&D intensity had a more pronounced impact on performance, supporting literature’s view on cultural differences in R&D strategies.
Vedoucí práce: Ladislav Tyll
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses